1948
DOI: 10.1021/ac60013a015
|View full text |Cite
|
Sign up to set email alerts
|

Selenium as Catalyst in Kjeldahl Digestions

Abstract: 1948 63 were analyzed mass-spectrometrically and found to contain not more than 0.5% of impurities. The results from the analysis of these mixtures, using the two procedures described above, are presented in Table I, which shows that the method yields accurate values over a wide range of concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1948
1948
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 31 publications
(24 reference statements)
0
10
0
1
Order By: Relevance
“…These conclusions are supported by Tables 10-12, which show that no nitrogen was lost when small amounts of selenium were used for Kjeldahl digestions involving the customary amounts of potassium sulphate even when digestion was prolonged, whereas there were losses when the quantity of selenium or the concentration of potassium sulphate was increased, particularly with long periods of digestion. Reports by Patel & Sreenivasan (1948) and Anantakrishnan & Srinivasa Pai (1952) that serious loss of nitrogen occurs even when small amounts of selenium are used with low concentrations of potassium sulphate could not be confirmed (Table 12; cf. results by standard method in Table 2 and by Piper's method in Table 6).…”
Section: Loss Of Sulphuric Acid During Kjeldahl Digestionmentioning
confidence: 94%
“…These conclusions are supported by Tables 10-12, which show that no nitrogen was lost when small amounts of selenium were used for Kjeldahl digestions involving the customary amounts of potassium sulphate even when digestion was prolonged, whereas there were losses when the quantity of selenium or the concentration of potassium sulphate was increased, particularly with long periods of digestion. Reports by Patel & Sreenivasan (1948) and Anantakrishnan & Srinivasa Pai (1952) that serious loss of nitrogen occurs even when small amounts of selenium are used with low concentrations of potassium sulphate could not be confirmed (Table 12; cf. results by standard method in Table 2 and by Piper's method in Table 6).…”
Section: Loss Of Sulphuric Acid During Kjeldahl Digestionmentioning
confidence: 94%
“…With regard to the catalyst, survey of the literature indicates that mercury is the only 'safe' catalyst, with which no losses have been reported (Bradstreet, 1965;Fleck & Munro, 196 j). Reports of losses with selenium or copper or mixtures of these date back to the 1930's (see Fleck & Munro, 1965) with adequate confirmation in 1948 (Hiller, Plazin & Van Slyke, 1948;Patel & Sreenivasan, 1948). T h e disadvantage of mercury is that it forms a mercury-ammonium complex which must be decomposed before determining ammonia.…”
Section: Kjeldahl Methodsmentioning
confidence: 99%
“…Reports of losses with selenium or copper or mixtures of these date back to the 1930's (see Fleck & Munro, 1965) with adequate confirmation in 1948 (Hiller, Plazin & Van Slyke, 1948;Patel & Sreenivasan, 1948). T h e disadvantage of mercury is that it forms a mercury-ammonium complex which must be decomposed before determining ammonia.…”
mentioning
confidence: 99%
“…The 1-hour afterboil is much less than that recommended by Shirley and Becker ( 12) and others (6, 7). Patel and Sreenivasan (8) found that if the afterboil were extended to 6 hours considerable nitrogen was lost. They found a mercuric oxide-selenium mixture to be a more effective catalyst than either alone when used on refractory nitrogen compounds.…”
Section: Literature Citedmentioning
confidence: 99%